Quantifying species recovery and conservation success to develop an IUCN Green List of Species. Issue 5 (18th April 2018) - Akçakaya, H. Resit; Bennett, Elizabeth L.; Brooks, Thomas M.; Grace, Molly K.; Heath, Anna; Hedges, Simon; Hilton‐Taylor, Craig; Hoffmann, Michael; Keith, David A.; Long, Barney; Mallon, David P.; Meijaard, Erik; et al.
Abstract: Stopping declines in biodiversity is critically important, but it is only a first step toward achieving more ambitious conservation goals. The absence of an objective and practical definition of species recovery that is applicable across taxonomic groups leads to inconsistent targets in recovery plans and frustrates reporting and maximization of conservation impact. We devised a framework for comprehensively assessing species recovery and conservation success. We propose a definition of a fully recovered species that emphasizes viability, ecological functionality, and representation; and use counterfactual approaches to quantify degree of recovery. This allowed us to calculate a set of 4 conservation metrics that demonstrate impacts of conservation efforts to date (conservation legacy); identify dependence of a species on conservation actions (conservation dependence); quantify expected gains resulting from conservation action in the medium term (conservation gain); and specify requirements to achieve maximum plausible recovery over the long term (recovery potential). These metrics can incentivize the establishment and achievement of ambitious conservation targets. We illustrate their use by applying the framework to a vertebrate, an invertebrate, and a woody and an herbaceous plant. Our approach is a preliminary framework for an International Union for Conservation of Nature (IUCN) Green List of Species, which was mandated by a resolution of IUCN members in 2012. Although there are several challenges in applying our proposed framework to a wide range of species, we believe its further development, implementation, and integration with the IUCN Red List of Threatened Species will help catalyze a positive and ambitious vision for conservation that will drive sustained conservation action. Abstract : Article impact statement : An objective and ambitious definition of species recovery and a system for recognizing conservation impact inform an IUCN Green List of Species.